Renewable energy adoption: a case of skill gaps in South African local government - Oladejo, Olufemi Michael; Shava, Elvin; Ndebele, Nduduzo Comfort (Frontiers in Sustainable Energy Policy, 2025)
The transition toward renewable energy systems is crucial in addressing the global challenge of climate change and reducing reliance on fossil fuels. Local governments play a pivotal role in driving this transition. As an arm of government closest to the grassroots, local governments are uniquely positioned to influence energy consumption patterns and ensure sustainable practices through local policies and regulations. Unlike federal initiatives that often focus on broad policy frameworks, local governments operate at the grassroots level, enabling them to influence energy policy directly, engage community stakeholders, and drive the implementation of renewable projects. However, to effectively promote renewable energy systems requires diverse skills among local government officials and staff. These include technical, policy formulation and regulation, finance management, etc. To understand the skills that will benefit renewable energy solutions within the communities, the study adopted a qualitative research methodology, which utilized face-to-face interviews guided by a semi-structured interview framework. Seven (7) stakeholders from South Africa's renewable energy sector were purposively selected to respond to interview questions. Data was collected using MS Teams, where it was recorded and later transcribed to Microsoft Word. Thematic analysis was applied to observe and understand the patterns in the data. The study results revealed that officials from selected local municipalities demonstrated a significant lack of necessary renewable energy skills, which triggers poor adoption of renewable energy and its implementation at the local government level. This underscored the ineffective renewable energy policies at the grassroots level and portrayed the need to develop the required skills at the municipality level to harness the social and economic opportunities that could be derived from utilizing renewable energy in communities. The study's conclusions emphasize the need for local government staff to be exposed to renewable energy training that helps build capacity through synergy and inclusive participation to ensure a successful renewable energy transition.